Substitution of the Fermented Cocoa Pod Waste in to the Grass Based Diet on Performance of Bligon Goat - Engkus Ainul Yakin; Sri Sukaryani; Catur Suci Purwati (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
This experiment was aimed to evaluate the effect of fermented cocoa pod as feed for Bligon goats. Sixteen Bligon goat with a body weight of 11-13 kg were put into individual cages which were equipped with feed and drink containers. The study design used a randomized block design, where initial body weight in as peragam with four treatments and four replications. Fermented cocoa pod used Trametes versicolor. The experimental treatments were T1= 30% of fresh king grass + 50% of dried king grass + 20% of concentrate; T2= 30% of fresh king grass + 30% of dried king grass + 40% of concentrate; T3= 30% of fresh king grass + 30% of cocoa pod + 40% of concentrate; and T4= 30% of fresh king grass + 30% of cocoa pod fermented + 40% of concentrate. Observed variables were feed intake, body weight gain and feed conversion. The result showed that fermented cocoa pod at the level of 30% had higher (P<0.05) infeed intake (560.33 g day-1), body weight gain (101.79 g head-1day-1), and feed conversion (5.50) compared to other treatments. The conclusion of this study were the use of 30% cocoa pod fermented in the ration showed the best body weight gain and feed conversion on Bligon goat performance.